3-D printed injection system for capillary electrophoresis. Issue 11 (7th March 2022) - Huge, Bonnie Jaskowski; Young, Kevin; Kerr, Caitlin; Champion, Matthew M.; Dovichi, Norman J.
Abstract : A robust and compact injection system for capillary electrophoresis that can be rapidly manufactured using 3-D printing technology. Abstract : Commercial systems for capillary electrophoresis are designed for the unattended analysis of several samples, and are usually large, complex, and expensive. We report a compact system for manual injection of a single sample in capillary electrophoresis, which is ideal for method development and for student training. The injector consists of two parts that are manufactured by three-dimensional printing (STL and STEP files are included as ESI 1 ). One part is immobile and holds an electrode for powering electrophoresis and a gas line for pressurized injection and pumping fluids through the capillary. The second part is removable and is used to hold washing solutions, separation electrolyte, or sample. Conventional machining is used to tap holes to hold the electrode, separation capillary, gas line, and safety interlock. The system is used for either pressure or electrokinetic sample injection, and can be used to pump fluids through the capillary for changing background electrolytes and reconditioning the capillary between runs. We coupled the injection system to our high-dynamic range laser-induced fluorescence detector and evaluated the system by performing capillary zone electrophoresis on solutions of fluorescein. Electrokinetic injection produced a linear response across five orders of magnitude dynamic range (slope of the log–log calibration curve was 1.02), concentration detection limits of 5 pM, and mass detection limits of 1 zmol. Pressure injection produced a linear response across at least four orders of magnitude (slope of the log–log calibration curve was 0.92), concentration detection limits of 2 pM, and mass detection limits of 10 zmol.